Sunan Sendang Duwur: Jejak penyebaran Agama Islam di pesisir Kabupaten Lamongan - Aprilita Faradina Suyatno; Lutfiah Ayundasari (Universitas Negeri Malang, 2021)
The dissemination of Islamic teachings in the north coastal area of Lamongan Regency to be precise in Sendang Duwur Village, Paciran District is closely related to the figure of Raden Noer Rochmat or known as Sunan Sendang Duwur. In spreading Islam, Sunan Sendang Duwur adopted the method of preaching culturally through acculturation of local culture with the values of Islamic teachings which can still be found from the reliefs of the mosque to the tomb of Sunan Sendang itself and is evidence of the spread of Islam on the coast of Lamongan Regency. His role in spreading Islam is very memorable in the collective memory of the surrounding community and is considered as one of the influential figures in the spread of Islam in Lamongan Regency. The purpose of this study was to find out more about the biography, role, and legacy of Raden Noer Rochmat or Sunan Sendang Duwur in spreading Islamic teachings in Sendang Duwur Village, Paciran District, Lamongan Regency. This study uses a qualitative research method with a historical approach by looking at and examining all aspects of life from Sunan Sendang Duwur ranging from biographies, roles, methods of preaching, to sites that are legacy of Sunan Sendang Duwur as traces of the spread of Islam in Lamongan. Penyebaran ajaran agama Islam di wilayah utara pesisir Kabupaten Lamongan tepatnya di desa Sendang Duwur Kecamatan Paciran erat kaitannya dengan sosok Raden Noer Rochmat atau yang dikenal dengan nama Sunan Sendang Duwur. Dalam menyebarkan agama Islam, Sunan Sendang Duwur mengadopsi metode dakwah secara cultural melalui akulturasi budaya lokal dengan nilai-nilai ajaran agama Islam yang masih dapat ditemukan peninggalannya dari mulai dari relief masjid hingga makam Sunan Sendang sendiri dan menjadi bukti penyebaran agama Islam di pesisir Kabupaten Lamongan. Peranannya dalam menyebarkan agama Islam sangat membekas dalam memori kolektif masyarakat sekitar dan dianggap sebagai salah satu tokoh yang berpengaruh dalam penyebaran agama Islam di Kabupaten Lamongan. Tujuan dari penelitian ini adalah untuk mengetahui lebih lebih lanjut tentang biografi, peranan, dan jejak peninggalan Raden Noer Rochmat atau Sunan Sendang Duwur dalam menyebarkan ajaran agama Islam di Desa Sendang Duwur, Kecamatan Paciran, Kabupaten Lamongan. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan sejarah dengan melihat dan mengkaji seluruh aspek kehidupan dari Sunan Sendang Duwur mulai dari biografi, peranan, metode dakwah, hingga situs-situs yang peninggalan Sunan Sendang Duwur sebagai jejak penyebaran agama Islam di Lamongan.